Differences and significance of peripheral blood interleukin-6 expression between patients with granulomatous lobular mastitis and those with benign breast tumors - Zhou, Yue; Wu, Jingjing; Ma, Lina; Wang, Bing; Meng, Tian; Chen, Hongfeng; Ye, Meina (Frontiers in Medicine, 2023)
Objective: It is unclear whether the mechanism of the interleukin (IL)-6 signalling pathway is similar between granulomatous lobular mastitis (GLM) and benign breast tumour. This study aimed to explore the differences and significance of peripheral blood IL-6 and related cytokines, routine blood test results, and C-reactive protein (CRP) levels between patients with GLM and benign breast tumour. Methods: 73 inpatients with GLM who underwent surgery and 60 patients with benign breast tumours diagnosed by pathological findings between November 2022 and May 2023 were included. The white blood cell (WBC) and neutrophil (NEU) counts were determined using an automatic blood cell analyser, CRP level was determined by immunoturbidimetric assay, and serum IL-6 and related cytokine levels were determined by enzyme-linked immunosorbent assay. Results: The WBC, NEU, and CRP values in patients with GLM were significantly higher than those in patients with benign breast tumour (P<0.01). Serum IL-6 levels were significantly higher in patients with GLM than in those with benign breast tumour (P<0.01). There were no significant differences in the serum concentrations of IL-1β, IL-7, and interferon (IFN)-γ between patients with GLM and those with benign breast tumour (P>0.05), but the tumour necrosis factor (TNF)-α level was higher in patients with GLM than in those with benign breast tumour (P<0.01). Pearson correlation analysis showed that in patients with GLM, the IL-6 level was positively correlated with NEU, NEU%, CRP, IL-17, and TNF-α values(P<0.01). Additionally, the IL-6 level was weakly positively correlated with WBC and IFN-γ values. Conversely, in patients with benign breast tumour, the IL-6 level was not significantly correlated with the aforementioned indicators in routine blood tests but was positively correlated with IL-17, IFN-γ, and TNF-α values (P<0.01). Conclusions: IL-6, NEU, NEU%, and CRP values were significantly elevated in patients with GLM compared with those with benign breast tumour, indicating that IL-6 plays an important role in the development and onset of GLM. The correlation between these cytokines and the development and progression of benign breast tumours needs to be explored further, as cytokines such as IL-6 may provide effective markers for the treatment of GLM.